2008
DOI: 10.1890/07-1155.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Ecology of North Atlantic Shores: Do Differences in Players Matter for Process?

Abstract: Abstract. The contrasting histories of the western and eastern shores of the North Atlantic Ocean provide an excellent opportunity to consider the implications of past events for present ecological processes and the functioning of marine ecosystems. Similarities and differences in assemblage composition have been driven by large-scale events, such as the trans-Arctic interchange, which has shaped the species pool, and cycles of glaciation, which have determined phases of local or regional extinction and coloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 223 publications
(248 reference statements)
5
63
0
Order By: Relevance
“…In contrast, McCook & Chapman (1991) found that Fucus was competitively dominant to mussels on shores in Canada during primary succession after ice scour, when grazers were rare. The impact of grazing intensity on fucoids at the different locations may have caused the differences in these results (see also Jenkins et al 2008). In the Mediterranean, Benedetti-Cecchi et al (1996) found no evidence of interactions between limpets and mussels in determining algal abundance, and each species had independent effects that were consistent among locations.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, McCook & Chapman (1991) found that Fucus was competitively dominant to mussels on shores in Canada during primary succession after ice scour, when grazers were rare. The impact of grazing intensity on fucoids at the different locations may have caused the differences in these results (see also Jenkins et al 2008). In the Mediterranean, Benedetti-Cecchi et al (1996) found no evidence of interactions between limpets and mussels in determining algal abundance, and each species had independent effects that were consistent among locations.…”
Section: Discussionmentioning
confidence: 96%
“…in Europe appear to be controlled by sublethal temperature effects of adult energetics, the southern limit of M. edulis on the east coast of the U.S. is controlled by lethal temperature effects on adult populations . This is likely because the east coast of the U.S. has a more continental climate (and, therefore, greater temperature extremes) than the west coast of Europe, which has a more coastal climate (Wethey 1985, Jenkins et al 2008, Bailey 2009). Thus, mechanisms can differ within the same species in different regions.…”
Section: Discussionmentioning
confidence: 99%
“…Biota-biota interactions are among the most important determinants of biodiversity. Thus, the composition of the biota has broad and deep effects on the character of shore zone ecosystems and the ecological services that they provide (Jenkins et al 2008).…”
Section: Biotamentioning
confidence: 99%